Survey of the approach to the diagnosis and management of bacterial pneumonia in adult horses by equine veterinarians - Hepworth-Warren, Kate L.; Love, Kim (Frontiers in Veterinary Science, 2024)
Bacterial pneumonia is a common disease in adult horses, but there are no guidelines for practitioners regarding risk factors, diagnosis, and management of the disease. The objectives of this study were to describe how a group of equine veterinarians diagnose and treat bacterial pneumonia in adult horses. A 22-question survey was distributed via multiple platforms to equine veterinarians asking questions regarding the frequency with which they identified specific clinical findings and used certain diagnostic modalities, and the approach to antimicrobial and adjunct therapy. Three hundred nine survey responses were received of which 244 were complete and used in the final analyses. There are significant differences in the ways that different equine veterinarians diagnose and treat bacterial pneumonia based on practice type and training of the practitioner. The majority of practitioners treat with antimicrobials for longer than 2 weeks, and only 53.3% of respondents reported that they “always” or “most of the time” used culture and antimicrobial susceptibility testing to guide therapy. There is a need for guidelines to reduce the duration of therapy and improve antimicrobial stewardship when treating bacterial pneumonia in horses.